Permeability factor, cytotoxicity and serotyping of Pseudomonas aeruginosa strains - Hostacká, A; Majtán, V (Folia microbiologica, 1992)
We analyzed in detail the permeability and cytotoxic activity as well as the serotypes of 127 Pseudomonas aeruginosa strains. Sixty-seven strains were isolated from immunocompromised patients (51 from patients with tumors and 16 from patients after transplantation) and 60 strains were isolated from patient's ears. Culture filtrates of strains isolated from patients after transplantation were responsible for the highest part of permeability reactions corresponding to an intermediate toxin production (68.8%) (categories 2 and 3) and culture filtrates of strains isolated from patients with tumors caused the highest percentage of permeability reactions corresponding to a strong toxin production. Culture filtrates of strains isolated from ears of patients were responsible for the highest percentage of negative permeability reactions (15%). With positive permeability reaction size (categories 2-6) increased also the percentage of cytotoxicity as well as the intensity of morphological changes on Vero cells after 1 and 2 d. We did not observe any relationship between a particular permeability reaction category and the most frequent serotypes (O4, O6) or nontypable strains of the tested groups.
Keywords: Serotyping; Humans; zevní ucho; Organ Transplantation; kapilární permeabilita; Vero buňky; buněčná smrt; Ear, External; lidé; zvířata; Capillary Permeability; Pseudomonas aeruginosa; Neoplasms; nádory; králíci; transplantace orgánů; Animals; Cell Death; Rabbits; Vero Cells; sérotypizace